Bis(butan-1-aminium) naphthalene-1,5-disulfonate - Jin, Yu (International Union of Crystallography, 2012)
In the title compound, 2C(4)H(12)N(+)·C(10)H(6)O(6)S(2) (2−), the anion lies on an inversion center, so the asymmetric unit contains half an anion and one cation which are linked by a strong N—H⋯O hydrogen bond. The crystal structure comprises discrete ions, which are linked into centrosymmetric R (4) (4)(12) loops by N—H⋯O interactions.